2019
DOI: 10.1103/physreve.99.033110
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Rayleigh-Taylor turbulence by time-periodic acceleration

Abstract: The dynamics of Rayleigh-Taylor turbulence convection in presence of an alternating, time periodic acceleration is studied by means of extensive direct numerical simulations of the Boussinesq equations. Within this framework, we discover a new mechanism of relaminarization of turbulence: The alternating acceleration, which initially produces a growing turbulent mixing layer, at longer times suppresses turbulent fluctuation and drives the system toward an asymptotic stationary configuration. Dimensional argumen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…The above phenomenon is also demonstrated by previous direct numerical simulations [16]. The heat transport suppression by the rotation is qualitatively different from that of rotating Rayleigh-Bénard (RB) convection by the rotating boundary force [6,16,36].…”
Section: B Effect Of Rotating On Global Quantities In Mixing Zonementioning
confidence: 57%
See 1 more Smart Citation
“…The above phenomenon is also demonstrated by previous direct numerical simulations [16]. The heat transport suppression by the rotation is qualitatively different from that of rotating Rayleigh-Bénard (RB) convection by the rotating boundary force [6,16,36].…”
Section: B Effect Of Rotating On Global Quantities In Mixing Zonementioning
confidence: 57%
“…The functional relation between Nu and Ra has been widely studied by direct numerical simulations in the RT turbulence [2,4,36].…”
Section: B Effect Of Rotating On Global Quantities In Mixing Zonementioning
confidence: 99%
“…Zen'kovskaya and Novosiadliy reported the high-frequency vibrational analyses for the case of immiscible two layer suspension [18]. Recently, an influence of time periodic alternating acceleration on the dynamics of Rayleigh-Taylor convection is carried out by Boffetta and co-workers where they utilized the numerically simulated Boussinesq equations [19].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, increasing attention has been given in recent years to Rayleigh-Taylor instability undergoing variable acceleration (see, in particular, Refs. [15][16][17][18][19][20][21][22]).…”
Section: Introductionmentioning
confidence: 99%
“…[17], and more recently, a number of studies have considered repeated cycling between acceleration and deceleration, as reported in Ref. [20].…”
Section: Introductionmentioning
confidence: 99%